The Anticoagulation in Patients with Atrial Fibrillation: Rivaroxaban and Warfarin - I. Yu. Koroleva; I. V. Kolesnichenko; V. P. Nosov; M. V. Zlobin; D. I. Abelevich (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of rivaroxaban compared with warfarin on the incidence of cardioembolic stroke and systemic thromboembolic complications (TEC), bleeding in patients with non-valvular atrial fibrillation (AF).Material and methods. Patients (n=126) older than 18 years, appealed to the Cardiology Clinic with non-valvular AF were included into an open non-randomized study. The patients were divided into 2 groups based on their socio-economic status: 77 patients received rivaroxaban and 49 - warfarin. The incidence of acute coronary syndrome, ischemic stroke and other TEC, bleeding as well as (only for patients taking warfarin) international normalized ratio (INR) and time in the therapeutic INR range were evaluated.Results. The incidence of ischemic stroke was not significantly different between groups, at the same time the incidence of other TEC was significantly higher in the warfarin group (0 vs 8%, p=0.011). The incidence of minor bleedings was significantly prevailed in warfarin group (0 vs 20%; p=0.0004). The time in the target INR range in the warfarin group was only 43%. 93.5% of patients continued to receive rivaroxaban after 9 months, and warfarin – 67.4% of patients.Conclusion. The results of our own clinical studies of rivaroxaban in patients with non-valvular AF have demonstrated efficacy comparable to that of warfarin. Rivaroxaban was superior to warfarin in safety.